Analysis of Time Delays in The Implementation of The Construction of A Light Brick Factory in Lamongan Using The Earned Value Method - M. Hery Indra Setiawan; Budi Witjaksana; Jaka Purnama (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Factory is an Industrial Building that processing raw material. This Light Weight Brick Factory Constructions will help the region to develop their economies further. In this case, the Lightweight Brick Factory Constructions have several problem that cause construction delays. This research was carried out because of delays in the lightweight brick factory construction project in Lamongan which was scheduled for completion in the 15th week with a contract value of IDR 1,835,474,186. in week 10 there was a delay of - 42.73%, week 11 there was a delay of - 42.66%, week 12 there was a delay of - 44.84%, week 13 there was a delay of - 48.08%, week 14 have a delay of -46.18%, and week 15 have a delay of -44.68% from the planned schedule. The results of the research analysis of the project Schedule Performance Index (SPI) at the 15th week of review were 0.55, indicating that the project was have a delays. These results show that the project was 11 weeks late out of the planned 16 weeks. The factor that made the project late in completion was the contractor or vendor because there were other problems that created a lack of cash flow